Potensi dan Upaya Mempertahankan Kefektifan Beberapa Entomopatogen dalam Mengendalikan Larva Oryctes rhinoceros Linn. di Perkebunan Kelapa Sawit - Henny Hendarjanti (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Hendarjanti H. 2021. The potential and efforts to maintain the effectiveness of several entomopathogens in controlling oryctes rhinoceros larvae in oil palm plantations. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 411-425. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Oryctes rhinoceros Linn. (Coleoptera: Scarabaeidae) is an essential oil palm pest. In the field, entomopathogenic control is less than optimal because the environmental conditions are not suitable. The purpose of this study was to determine the potential and efforts to maintain the effectiveness of Metarhizium anisopliae and Entomopathogens Nematodes (EPNs) for controlling O. rhinoceros larvae in oil palm plantations. The research has been conducted in immature oil palm plantations in Indragiri Hulu, Riau. The study used a non-factorial randomized block design with five treatments and three replications (EPNs: palm fronds mulch + no watering, palm fronds mulch + watering, palm fronds mulch + gunny sack + watering, Metarhizium anisopliae: palm fronds mulch + gunny sack + watering and control). Application of M. anisopliae with conidia density (1x106) with a dose of 0.15 l/m2 and EPNs 20,000 ij/m2. The application was carried out at the breeding site of rhinoceros beetle by spraying using a knapsack sprayer in the afternoon. The results showed that the pathogenicity of EPNs and M. anisopliae to larvae was 70.00 – 76.67% on the 24th day after application. On the first day after treatment, there was the death of larvae by EPNs. Application of M. anisopliae on larvae achieved death four days after application. The process of pathogenicity of EPNs in larvae was faster than that of M. anisopliae. The results showed that EPNs and M. anispoliae had an excellent opportunity to control O. rhinoceros and could be developed as an environmentally friendly and sustainable biological control.